Pengaruh Cookies Temvita Sebagai Snack Sehat Terhadap Kadar Haemoglobin Remaja Putri Dengan Anemia - Rahmadona Rahmadona; Mardiah Mardiah; Nurniati Tianasia Rullyni; Respatiningrum Respatiningrum; Ristina Rosauli Harianja (LPPM Universitas Muhammadiyah Riau, 2022)
Adolescence is a transition period from childhood to adulthood. The adolescent phase is characterized by physiological maturity, making adolescents need optimal nutrient intake for growth and development. An imbalance between intake needs and adequacy will cause nutritional problems. One of the main problems experienced by adolescents was iron deficiency anemia. The provision of nutrients or highly nutritious foods in the form of cookies from processed tempeh which has rich in fiber and iron is expected to overcome the problem of anemia. This study was aim to determine the effect of giving Temvita cookies as a healthy snack on hemoglobin (Hb) levels in adolescent girls with anemia. This research is a quasi-experimental study with one group pre-test-post-test design on 36 samples taken using the purposive sampling technique. This study was conducted from May to November 2019. Data were analyzed using an independent samples t-test. The results showed the average Hb score before giving Temvita cookies was 9.7 g/%, while after giving Temvita cookies was 11.2 g/%. Independent samples t-test results obtained a p-value of 0,024. The study concludes that there was an effect of giving Temvita cookies to adolescent girls with anemia on hemoglobin (Hb) levels. Hopefully, Temvita cookies could be an alternative healthy snack to increase adolescent Hb levels.